2015
DOI: 10.1016/j.otsr.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous correction of second toe proximal deformity: Proximal interphalangeal release, flexor digitorum brevis tenotomy and proximal phalanx osteotomy

Abstract: We report the results of a percutaneous technique to correct a proximal plantar flexion deformity of the second toe that combines several procedures: tenotomy of the Flexor Digitorum Brevis, plantar capsulotomy for release of the proximal interphalangeal joint and proximal phalangeal osteotomy. The goal of these procedures is to improve anatomical correction and preserve articular range of motion. From 2009 to 2011, 54 patients, mean age 64.4 years old (43-81) underwent surgery for a proximal deformity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The treatments of lesser toes deformities by MIS are mostly based on soft tissue release, such as joint capsulotomies and tenotomies. The procedures on the bone depend on the residual deformities, the reducibility, and the toe length [11, 19, 20]. Some authors use complete osteotomies for the correction of digital deformities [21, 22], others perform unicortical osteotomies in certain pathologies [16, 23], but all of them follow the same protocol starting correction with soft tissue techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The treatments of lesser toes deformities by MIS are mostly based on soft tissue release, such as joint capsulotomies and tenotomies. The procedures on the bone depend on the residual deformities, the reducibility, and the toe length [11, 19, 20]. Some authors use complete osteotomies for the correction of digital deformities [21, 22], others perform unicortical osteotomies in certain pathologies [16, 23], but all of them follow the same protocol starting correction with soft tissue techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This selective tenotomy sustains the grasping function of the toes. In the year 2015, a paper published by Frey et al (20) reported their results from a series of 57 feet presenting an isolated second toe PIPJ deformity without metatarsalgia or DIP deformity treated with a selective FDB tenotomy, plantar PIPJ release, and P1 osteotomy. In 42% of cases, extensor tenotomy was the choice.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-six percent of the lesser rays had retained active plantar flexion compared to 74% of the lesser rays who were semi-rigid or rigid before the surgery. A revision was reported only in 2 cases (3.5%) in which PIPJ fusion was carried out (20).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous toe corrections are a combination of small gestures including soft tissue procedures and osteotomies. 3,[12][13][14][15] The soft tissue procedures consist of detachments of tendons from the bone, tenotomies, and capsulotomies. Osteotomies can be performed in different directions.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…The most common are hallux valgus, bunionette, metatarsalgia, and toe deformities. Percutaneous toe corrections are a combination of small gestures including soft tissue procedures and osteotomies 3,12–15. The soft tissue procedures consist of detachments of tendons from the bone, tenotomies, and capsulotomies.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%